2021
DOI: 10.1186/s40168-020-00939-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive universal detection of blood parasites by selective pathogen-DNA enrichment and deep amplicon sequencing

Abstract: Background Targeted amplicon deep sequencing (TADS) has enabled characterization of diverse bacterial communities, yet the application of TADS to communities of parasites has been relatively slow to advance. The greatest obstacle to this has been the genetic diversity of parasitic agents, which include helminths, protozoa, arthropods, and some acanthocephalans. Meanwhile, universal amplification of conserved loci from all parasites without amplifying host DNA has proven challenging. Pan-eukaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 48 publications
3
54
0
Order By: Relevance
“…The tools used in the study shown in Table 1 were tested on their performance to identify viral elements from assembled contigs in the simulations. The tools used in this study to identify viral contigs were Vibrant (Version 1.2.0), VirSorter, VirSorter2, VirFinder, DeepVirFinder, MetaPhinder, Kraken 2, Phybrid, and a BLAST search using identified proteins from the Earth Virome Pipeline [ 15 , 16 , 19 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tools used in the study shown in Table 1 were tested on their performance to identify viral elements from assembled contigs in the simulations. The tools used in this study to identify viral contigs were Vibrant (Version 1.2.0), VirSorter, VirSorter2, VirFinder, DeepVirFinder, MetaPhinder, Kraken 2, Phybrid, and a BLAST search using identified proteins from the Earth Virome Pipeline [ 15 , 16 , 19 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…MetaPhinder, Phybrid, Phybrid Proteins, and Vibrant were run with default parameters [ 13 , 15 ]. Double-stranded DNA phages and single stranded DNA viruses were selected with the groups parameter of VirSorter2 as described by the authors [ 16 ]. Kraken 2 was run with default parameters using the minikraken database from March 2020 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, sparse but viable microbiota have been identified in the fetal gut at mid-gestation in humans [ 75 ]. However, this clinical study has been recently heavily criticised by other researcher of the field [ 103 , 104 ] who claim that contamination of the samples during analysis is the most probable explanation for the bacteria found in the fetal gut. Researchers who analysed meconium (the first faecal sample of the new-born) found low amounts of viable bacteria present but confirmed that the main bacterial colonization of the gut happens at the time of birth [ 105 ].…”
Section: Early Nutrition-microbiota Crosstalk In Sensitive Time Wimentioning
confidence: 99%
“…NGS has been used for the detection of Leishmania in the bone marrow of visceral leishmaniasis,[ 77 ] accurate diagnosis of neurocysticercosis infection in patients with atypical clinical manifestations,[ 78 ] diarrheal infections,[ 74 ] and detection of blood-borne helminths and protozoa. [ 79 80 ]…”
Section: Molecular Testing Strategiesmentioning
confidence: 99%